THE ROLE OF THE PROTOCOL DIVISION IN COORDINATING THE MAYOR OF BANDAR LAMPUNG'S AGENDA - Abdillah Hafizh; Tina Miniawati Barusman (International Journal of Multidisciplinary Reseach, 2026)
The complexity of local executive activities requires agenda coordination that is rapid, accurate, and adaptive. This study analyzes the role of the Protocol Division in coordinating the work agenda of the Mayor of Bandar Lampung, focusing on information, activity, and resource coordination, while identifying major constraints and corrective efforts. A descriptive qualitative approach was employed at the Protocol Division of the Bandar Lampung City Secretariat. Data were collected through in-depth interviews, observation, and document review involving purposively selected informants. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña and validated through triangulation. The findings show that the Protocol Division acts as a coordination hub by collecting, verifying, and aligning information; prioritizing activities and preventing scheduling conflicts; and coordinating personnel, facilities, and infrastructure in accordance with protocol standards. Coordination effectiveness is constrained by delayed or incomplete information, sudden agenda changes, competing priorities among regional agencies, and limited staffing. Stronger verification procedures, adaptive scheduling, early-stage communication, and improved resource capacity are therefore required to maintain the order, continuity, and effectiveness of the mayoral agenda.